The Proof of the Pudding Is in the Making: Reflections on Social Justice Teacher Education in English Language Teaching - Eleni Louloudi; Peter Schildhauer (Die Materialwerkstatt)
This contribution proposes five fundamental elements of social justice teaching as applied in language teacher education. It does so by taking into consideration already existing university formats – a seminar and a student-conference – which were built on the foundation of critical literacy pedagogies. By defining these elements, our goal is not only to prompt a discussion about social justice in language teacher education, but to center our students’ authentic voices and opinions about their own learning experiences.